Extraordinarily polymorphic microsatellite DNA in barley: species diversity, chromosomal locations, and population dynamics. - Saghai Maroof, M A (1994)
This study was undertaken to assess the extent of genetic variation in barley simple sequence repeats (SSRs) and to study the evolutionary dynamics of SSR alleles. SSR polymorphisms were resolved by the polymerase chain reaction with four pairs of primers. In total, 71 variants were observed in a sample of 207 accessions of wild and cultivated barley. Analyses of wheat-barley addition lines and barley doubled haploids identified these variants (alleles) with four loci, each located on a different chromosome. The numbers of alleles detected at a locus corresponded to the number of nucleotide repeats in the microsatellite sequences. The numbers of alleles at two loci were 28 and 37; to our knowledge these are the largest numbers of alleles for single Mendelian loci reported in plants. Three alleles were resolved by each of the other two loci. Allelic diversity was greater in wild than in cultivated barley and surveys of two generations (F8 and F53) of Composite Cross II, an experimental population of cultivated barley, showed that few of the alleles present in the 28 parents survived into generation F53, whereas some infrequent alleles reached high frequencies. Such changes in frequency indicate that the chromosomal segments marked by the SSR alleles are under the influence of natural selection. The SSR variants allow specific DNA sequences to be followed through generations. Thus, the great resolving power of SSR assays may provide clues regarding the precise targets of natural and man-directed selection.